Fluorination effects on the thermodynamic, thermophysical and surface properties of ionic liquids - Vieira, N. S. M.
This paper reports the thermal, thermodynamic, thermophysical and surface properties of eight ionic liquids with fluorinated alkyl side chain lengths equal or greater than four carbon atoms. Melting and decomposition temperatures were determined together with experimental densities, surface tensions, refractive indices, dynamic viscosities and ionic conductivities in a temperature interval ranging from (293.15 to 353.15) K. The surface properties of these fluorinated ionic liquids were discussed and several thermodynamic functions, as well as critical temperatures, were estimated. Coefficients of isobaric thermal expansion, molecular volumes and free volume effects were calculated from experimental values of density and refractive index and compared with previous data. Finally, Walden plots were used to evaluate the ionicity of the investigated ionic liquids. (C) 2016 Elsevier Ltd. All rights reserved.